"METHODOLOGICAL POSSIBILITIES OF PSYCHOLOGICAL GAMES IN GUIDING CHILDREN TO INDEPENDENT THINKING" (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The process of independent thinking in the world is viewed as the product and injection of the opportunities and freedoms that society creates for man. Independent thinking, on the other hand, is a process of personal cognitive activity and is characterized by a direct and integrated reflection of reality. Therefore, independent thinking incorporates interdisciplinary research and complex subjects. Since then, in the field of preschool education organization (MTT), it is considered one of the most important issues on the agenda of teaching children to think independently, cultivating their oral discourse, and engaging them in reading.